TERMINAL TIPE B SIMPANG EMPAT BANJARBARU - Hijrina, Sayda Noor; Febrita, Yuswinda (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Banjarbaru the capital of South Kalimantan Province, is showing good economic growth with the support of the Banjarbakula Metropolitan Area program, connecting Banjarmasin City, Banjarbaru City, Banjar Regency, Barito Kuala Regency and Tanah Laut Regency. In efforts to realize this program, efficient transportation facilities are key, especially terminals that are able to overcome human and vehicle circulation conflicts and increase accessibility within the site. The Type B terminal at Simpang Empat Banjarbaru adopts the Integrated Circulation concept with a focus on human and mode circulation. The integrated circulation concept is implemented in the form of buildings that can be reached by all groups, disabled or normal, as well as various modes of transportation. In principle, this concept is integrated into the terminal design using programming methods, creating an orderly and functional circulation. With an integrated terminal, people can enjoy smoother transportation services, programming makes various circulations and space functions structured and orderly for inside and outside the building so as to create circulation that does not cross.